DIAGNOSIS AND TREATMENT OF CARDIOVASCULAR DISEASES DURING PREGNANCY 2018. NATIONAL GUIDELINES - artiсle Editorial (Российский кардиологический журнал)
Developed by the Committee of experts of the Russian society of cardiology (RSC). Section of cardiovascular diseases in pregnant women